Lipopolysaccharide activation of human endothelial and epithelial cells is mediated by lipopolysaccharide-binding protein and soluble CD14. - Pugin, J (1993)
Myeloid cell activation by lipopolysaccharides (LPS) involves two proteins, plasma LPS-binding protein (LBP) and cell-membrane CD14. Cell membrane CD14, anchored by a glycerophosphatidylinositol tail, is the cellular receptor for LPS-LBP complexes. Another form of CD14, without the lipid tail, circulates as a soluble plasma protein. In this work we show that soluble CD14 (sCD14) is required for activation of endothelial and epithelial cells by LPS. We propose that LPS-LBP complexes transfer LPS to sCD14, and the LPS-sCD14 complexes then bind to a cellular receptor. Support for this pathway comes from experiments in which LBP and CD14 in normal human serum are blocked by specific antibodies, experiments in which serum is replaced by purified LBP and sCD14, and experiments in which specific binding of [3H]LPS to epithelial cells is quantitated.